Lymphogranuloma venereum: a retrospective analysis of an emerging sexually transmitted disease in a Lisbon Tertiary Center. (13th May 2021) - Neves, J.M.; Ramos Pinheiro, R.; Côrte‐Real, R.; Borrego, M.J.; Rodrigues, A.; Fernandes, C.
Abstract: Background: Lymphogranuloma venereum (LGV) is a sexual transmitted infection (STI), currently endemic within the population of men who have sex with men (MSM) of Western Countries. L2B variant has been reported as the predominant strain in the current LGV epidemics, although a shift towards L2‐434 has been observed in some European countries. Objectives: To evaluate and characterize the population with LGV infection diagnosed in Centro Hospitalar Universitário de Lisboa Central, Lisbon, Portugal. Methods: A retrospective analysis of all LGV diagnoses between 2016 and 2019 was performed. The diagnosis was established through ompA‐genotyping of samples yielding a positive result to Chlamydia trachomatis (CT). All considered samples were retrieved from the clinician activity, through swabbing and urine analysis and CT infection diagnosis was obtained using real‐time PCR. Results: During the period studied 16 279 CT diagnostics tests were employed, with a striking increase from 2016 ( n  = 467) to 2019 ( n  = 9362). A total of 1602 diagnoses of CT were established, from which 168 (10.5%) corresponded to LGV, with both infections showing a rising evolution, between 2016 and 2019, of 2.9 and 2.7 times, respectively. The majority of the LGV strains were genotyped as L2/434 (67.3%; n  = 113). LGV predominantly affected MSM and men who have sex with men and women (97.0%; n  = 163). Anorectal infection was the most prevalent one (90.5%; n  = 152), being proctitis the main clinical presentation (76.2%; n  = 128). Absence of symptoms was reported in almost 15% of the cases ( n  = 24). The presence of concomitant infection with human immunodeficiency virus was dominant (73.2%; n  = 123) and the prevalence of one or more STI co‐infections was about 60.1% ( n  = 99). Conclusions: An increasing evolution of CT and LGV testing and diagnosing was observable throughout the studied period. Characteristics of the population are similar with those described within LGV epidemics. In accordance with recent European studies, predominance towards L2 genotype was identified. Abstract : Linked Commentary : G. Ciccarese et al. J Eur Acad Dermatol Venereol 2021; 35 : 1606–1607. https://doi.org/10.1111/jdv.17468 .